THE USE OF CHILD ALERT ALARM AS AN EFFORT TO PREVENT VIOLENCE OF SEXUAL ABUSE IN CHILDREN IN THE OUTSIDE WORLD - Nugraheni, Alfirda Dewi (BELIA: Early Childhood Education Papers, 2019)
Cases of violence are a very detrimental threat to the future of Indonesia's generation, most victims of violence are children and women committed by those closest to them. The survey conducted by Komisi Perlindungan Anak Indonesia shows that sexual violence against children ranks first among other cases of violence. After the reporting of cases of sexual harassment that occurred at Jakarta International School, it made all parties worried. Anticipating child protection that has been developed by the Japanese state by implementing an alarm called "Bohan buza". The research method used is descriptive qualitative from various relevant sources. The application of alarm technology is an effort to prevent children from sexual violence in public places.